Providing Adaptive User Interfaces in Deviceless Learning Environments (International Conference on Computers in Education, 2022)
While smart devices such as smartphones and tablets have become indispensable in educational settings, many studies have mentioned related issues such as significant operational costs and low pedagogical effects. Additionally, the problem of inadequate area of students’ desk that results in no vacant desk space to place a smart device in addition to learning materials on the desk, that makes it difficult to utilize IT in educational settings, is highly relevant to current times. Consequently, to realize deviceless learning environments, the author of this paper designed “Followable Learning Environment (FLE)”. Because the mechanism of FLE is similar to projection-based AR techniques, it can freely control the size and shape of projected user interfaces (UIs). This paper presents methods of detecting the area of blank space onto a student’s desk and project UIs that adapt size and shape into the space.